Effects of Laparoscopic Roux-en-Y Gastric Bypass on Anthropometric Characteristics, Hypertension, Type 2 Diabetes Mellitus and Metabolic Syndrome: An Iranian Experience: - Zamani, Mohammad Mahdi; Ghoghaei, Morteza; Khajeh, Elias; Taghdiri, Foad; Taghdiri, Soudeh; Sedaghat, Mojtaba; Toolabi, Karamollah (Galen Medical Journal, 2014)
Background: Surgically induced weight loss is a treatment option for the management of obesity and the related common disorders. This study evaluated the beneficial effects of bariatric surgery on metabolic profile and the prevalence of metabolic syndrome (MetS) among Iranian patients. Materials and Methods: A prospective observational study was performed on 26 morbidly obese patients scheduled for bariatric surgery, using laparoscopic Roux-en-Y gastric bypass (LRYGB). The parameters of hypertension, type 2 diabetes mellitus (T2DM), hyperlipidemia, MetS prevalence, and anthropometric measurements of Iranian patients, were recorded, at the preoperative visit and in follow-ups. The follow-up was performed for a median of 12 months, and the change in MetS prevalence and its componnts were assesed. Results: LRYGB induced a mean weight loss of 69.0±21.2%, after 12 months. Preoperative MetS was diagnosed in 21 patients (84%) and decreased to 6 patients (24%) after LRYGB (P=0.001). Likewise, the prevalence of hypertension was significantly decreased from 76% (pre-LRYGB values) to 20% (post-LRYGB values) (P=0.001). The prevalence of T2DM was also decreased from 20% to 8% (P=0.5). Conclusion: According to our results, RYGB produced a rapid and significant weight loss and improvement in hypertension and MetS within one year but there was a controversy about the improvement of T2DM, in Iranian morbidly obese patients.